2021
DOI: 10.1172/jci133525
|View full text |Cite
|
Sign up to set email alerts
|

CLIC1 recruits PIP5K1A/C to induce cell-matrix adhesions for tumor metastasis

Abstract: Membrane protrusion and adhesion to the extracellular matrix, which involves the extension of actin filaments and formation of adhesion complexes, are the fundamental processes for cell migration, tumor invasion, and metastasis. How cancer cells efficiently coordinate these processes remains unclear. Here, we showed that membrane-targeted CLIC1 spatiotemporally regulates the formation of cell-matrix adhesions and membrane protrusions through the recruitment of PIP5Ks to the plasma membrane. Comparative proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Therefore, the tumorigenesis and progression of HCC are indispensably influenced by hormones including AR. Recently an article uncovered that the mechanism of olaparib and enzalutamide in suppressing HCC progression is partially owing to the AR-mediated BRCA1 signaling pathway [ 31 , 32 ]. Another study also demonstrated that AR dramatically reduced the HCC invasion and migration by targeting the miR-325/ACP5 pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tumorigenesis and progression of HCC are indispensably influenced by hormones including AR. Recently an article uncovered that the mechanism of olaparib and enzalutamide in suppressing HCC progression is partially owing to the AR-mediated BRCA1 signaling pathway [ 31 , 32 ]. Another study also demonstrated that AR dramatically reduced the HCC invasion and migration by targeting the miR-325/ACP5 pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This channel is upregulated in various cancer type such as prostate [ 46 ], gallbladder (GBC) [ 48 ], colon cancer [ 47 ], gastric [ 49 ], clear cell renal cell carcinoma [ 50 ], and glioblastoma stem cells [ 51 , 52 ]. Overexpressed CLIC1 in patients with HCC [ 53 ] positively correlates with HCC proliferation and metastasis [ 54 ]. CLIC1 participates in hypoxia-induced colonic carcinoma metastasis via the MAPK/ERK pathway [ 45 ].…”
Section: Membrane-associated Components Of Chloride Movementmentioning
confidence: 99%
“…CLIC1 participates in hypoxia-induced colonic carcinoma metastasis via the MAPK/ERK pathway [ 45 ]. Moreover, CLIC1 is recruited to the plasma membrane in response to chemotaxis, such as directional treatment with epidermal growth factor (EGF) and mechanotaxis and its ectopic expression of CLIC1 enhances migratory apparatus such as lamellipodia and invadopodia [ 54 ]. Hypoxia-induced tumor cells possess irregular microvascular networks and blood flow [ 55 ] and can be transformed to promote cancer metastasis [ 56 ].…”
Section: Membrane-associated Components Of Chloride Movementmentioning
confidence: 99%
“… 60 Related research has shown that CLIC-1 is highly expressed on the tumor cells of a variety of human cancers, and it is involved in tumor progression and metastasis. 70 Studies have shown that CLIC-1 can shuttle between the cytoplasm and cell membrane, and participate in the process of regulating cell adhesion to the extracellular matrix. This process is achieved by CLIC-1 regulating the new extracellular matrix through the PIP5Ks signaling pathway.…”
Section: Inflammatory Factors Apoptosis and Pyroptosis In Oamentioning
confidence: 99%
“…This process is achieved by CLIC-1 regulating the new extracellular matrix through the PIP5Ks signaling pathway. 70 TME16A and CLCA1 are Ca 2+ -activated chloride channels that have been discovered recently. 71 , 72 Previous studies have shown that they participate in the enhancement of the production and secretion of inflammation mucus in the airway, which is regulated by high levels of IL-13.…”
Section: Inflammatory Factors Apoptosis and Pyroptosis In Oamentioning
confidence: 99%